The Use Of Adjuvant Therapies For Tonsillectomy - Hassan, Hussein M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: The aim was to ascertain the current practice of adjuvant therapy for tonsillectomy and to determine whether it is evidence based.Methods: A questionnaire answers were obtained from sixty otolaryngologists in Baghdad.Results: There was no any enthusiasm for routine intra-operative local anaesthesia. Paracetamol (Acetaminophen) is prescribed by nearly all surgeons for postoperative analgesia,and the current literature supports its efficacy and safety. Further, some practitioners combine paracetamol with NSAIDs, and/or Tramadol-Opioids. Evidence to support the additional use of these agents is, however non existent or limited. For the use of antibiotics, we found some of the otolaryngologists do use a course of few days of pre-operative antibiotics and almost all of them do give postoperative antibiotics for seven-ten days. Some aspects of tonsillectomy care are uniform and evidence based. Others are heterogenous and suffer from lack of adequate data in the literature.